Effect of planting method on C:N:P stoichiometry in soils, young silver fir (Abies alba Mill.) and stone pine (Pinus cembra L.) in the upper mountain zone of Karpaty Mountains - Jarosław Lasota (Elsevier, 2021)
C/N/P stoichiometry offers important indicators of ecosystem function and productivity. The aim of this research was to determine how planting methods in biogroups influence C/N/P stoichiometry in soil and plants. We hypothesised that planting methods, consisting in different initial spacing and shape would affect the growth characteristics of trees, and consequently, change soil properties – microbiological activity, in particular. This research examined two species that have different ecological requirements, silver fir (Abies alba Mill.) and Swiss stone pine (Pinus cembra L.), grown in the upper mountain zone, 1200 m above sea level. We established 48 experimental plots with two planting methods and two species in 2011. The soil and plant samples for laboratory analysis were taken in September 2020. In the first planting method 49 seedlings at regular 1 × 1 m spacing in a square plot (PM1) were planted, while in the second method 50 seedlings in two rhombus plots with 50 × 50 cm spacing (PM2) were planted. We determined the basic physicochemical properties and enzymatic activity in soil samples, and we recorded the content of C, N and P in testing needle samples from the trees. We also calculated the C/N, C/P and N/P ratios for both the soil samples and the plants. We found that the formation of biogroups with smaller spacing during stand renewal influenced the selected soil properties; within the biogroups with smaller spacing, an increase in soil biochemical activity was found. Our research confirms that planting methods and species are essential contributors to the C/N/P stoichiometry of soils and plants. The C/N/P stoichiometry of the soil samples from the different species and the different planting methods ranged between 928/37/1 and 1087/42/1. In the case of the Swiss stone pine needles, we noted a narrower C/N/P stoichiometry compared to the fir needles, regardless of the planting method. C/N/P stoichiometry is a useful tool for reflecting the nutrient cycle in mountain ecosystems, and our research shows that in the case of species with higher ecological requirements, stoichiometry can indicate nutrient limitation. In higher mountainous locations, nitrogen and phosphorus deficiencies are the main limiting factor. In the case of fir trees, the method of planting helps to reduce nutrient limitation and improve growth characteristics.